2017
DOI: 10.18203/2349-2902.isj20174898
|View full text |Cite
|
Sign up to set email alerts
|

Outcome analysis of low pressure versus high pressure pneumoperitoneum laparoscopic cholecystectomy: a randomized clinical study

Abstract: Background: Laparoscopic cholecystectomy is established as gold standard for management of cholelithiasis. Intraoperative pneumoperitoneum affects the postoperative outcomes. The current stress is on increasing patient safety. Hence, this prospective study was undertaken to compare the effect of low pressure pneumoperitoneum (LPP <10 mm Hg) versus high pressure pneumoperitoneum (HPP > 14 mm Hg) on postoperative pain and ileus.Methods: 120 patients undergoing laparoscopic cholecystectomy were randomized i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…For example, a prospective randomized trial comparing standard pressure versus low-pressure LC was done in a tertiary care hospital in Kolkata, India, in which Ghosh, Gangopadhyay, 14 have accessed post-operative pain by VAS score at 6 hours, 12 hours and 24 hours post-operatively and concluded that there was a significant difference in pain at 6, 12 and 24 hours in low-pressure pneumoperitoneum as compared to high-pressure pneumoperitoneum. Similarly, it was concluded by Mahajan et al, 5 five that low pressure (less than 10 mmHg) pneumoperitoneum is not only a safe approach with similar outcomes when compared to high pressure (more than 14 mmHg), but it is also associated with lesser post-operative pain. Likewise, in the studies mentioned earlier, in our study, more patients who were operated on under high pneumatic pressure (>15 mmHg) had complaints of abdominal pain as compared to the low-pressure group (8-12 mmHg).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…For example, a prospective randomized trial comparing standard pressure versus low-pressure LC was done in a tertiary care hospital in Kolkata, India, in which Ghosh, Gangopadhyay, 14 have accessed post-operative pain by VAS score at 6 hours, 12 hours and 24 hours post-operatively and concluded that there was a significant difference in pain at 6, 12 and 24 hours in low-pressure pneumoperitoneum as compared to high-pressure pneumoperitoneum. Similarly, it was concluded by Mahajan et al, 5 five that low pressure (less than 10 mmHg) pneumoperitoneum is not only a safe approach with similar outcomes when compared to high pressure (more than 14 mmHg), but it is also associated with lesser post-operative pain. Likewise, in the studies mentioned earlier, in our study, more patients who were operated on under high pneumatic pressure (>15 mmHg) had complaints of abdominal pain as compared to the low-pressure group (8-12 mmHg).…”
Section: Discussionmentioning
confidence: 65%
“…Besides, it may cause post-operative pain due to peri-toneal irritation, and its use is associated with immunological impairment. 5,6 The increased intra-abdominal pressure (IAP) is associated with cardiopulmonary complications such as tachycardia, cardiac arrhythmias, pulmonary oedema, and reduced hepatic and renal blood flow. Decrease hepatic blood flow can cause hepatic injury and raised liver enzymes level, while decreased renal blood flow can lead to kidney injury and oliguria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation